Ideal Traffic Accident Crime Case Resolution based on Restorative Justice - Adi Kurnia Setiadi; Fauzie Yusuf Hasibuan; Maryano Maryano (Ridwan Institute, 2023)
· This study focuses on the first problem of solving traffic accident criminal cases that have been applied in law enforcement and how to reconstruct the ideal traffic accident crime resolution based on a restorative justice approach. The method used in this study is normative juridical research with a research approach in the form of a normative approach. The result of this study is that the settlement of criminal cases of traffic violations in Indonesia to date (ius constitutum), basically still prioritizes conventional legal approaches and criminal sanctions. Cases of traffic accident violations are processed and resolved within the framework of the criminal justice system normally, starting from the police, prosecutor's office, and court levels, according to the criminal procedure law, (2) Reconstruction of the settlement of traffic accident violations is very likely to be applied in Indonesia with several non-litigation models (mediation), namely the independent perpetrator-victim mediation approach and perpetrator-victim mediation involving law enforcement (restorative justice agencies). Settlement efforts through the courts can only be pursued if restorative efforts fail to reach an agreement. With these results, it is suggested: (1) The police, prosecutors, and courts should be more intensive to socialize and provide education related to the application of restorative justice, especially for traffic accident crimes, (2) The principle of restorative justice needs to be realized in the main legal form, namely a law that comprehensively and integratively covers the regulation of all components of the criminal justice system.